ANALYZING MISCONCEPTION ABOUT EARTH AND SOLAR SYSTEM HELD BY JUNIOR HIGHSCHOOL STUDENTS IN CENTRAL BANDUNG REGION USING A FOUR-TIER DIAGNOSTIC TEST - Imtiyaz, Nisrina Zakiyyah; Rusyati, Lilit; Rustaman, Nuryani (Universitas Pakuan, 2025)
The difference between students' conceptions and science concepts is known as misconceptions. One of the topics that has a high percentage of misconceptions is the topic of Earth and Solar System. Therefore, further research is needed in evaluating misconceptions on this topic. This study aims to analyze the types of conceptions and common misconceptions in each subtopic in the Earth and Solar System topic. The instrument used was the Four-Tier Diagnostic Test. The research method used was quantitative research method, with cross-sectional survey design. The sample in this study consisted of 904 grade 8 junior high school students in the Central Bandung Region. The results showed that there are three types of conceptions with the highest percentage, namely Lack of Knowledge (29%), Scientific Knowledge (26%), and Misconception (24%). From these results, it can be seen that the number of misconceptions among students in this topic is still relatively high, especially in the concept of planets (35%), earth movement in solar system (23%), and sun characteristics (39%). These results indicate that junior highschool students have three higher conception, with common misconceptions were found in the concept of planets, earth movement in science, and characteristics of the sun.